Raw ship-based Multibeam Sonar Data from the Amundsen Sea acquired during R/V Nathaniel B. Palmer expedition NBP1005 (2010) ... - Yager, Patricia (Interdisciplinary Earth Data Alliance (IEDA), 2013)
This data set was acquired with a ship-based Kongsberg EM120 Multibeam Sonar system during Nathaniel B. Palmer expedition NBP1005 conducted in 2010 (Chief Scientist: Dr. Patricia Yager). These data files are of MBSystem Compatible format and include Swath Bathymetry, Acoustic Backscatter, and Sidescan data that have not been processed. Data were acquired as part of the project(s): ASPIRE (Amundsen Sea Polynya International Research Expedition), and funding was provided by NSF grant(s): ANT08-39069. ...